Physical modelling of the combined effect of vegetation and wood on river morphology - Bertoldi, W.; Welber, M.; Gurnell, A.M.; Mao, L.; Comiti, F.; Tal, M. (Geomorphology (Amsterdam, Netherlands), 2015)
The research reported in this paper employs flume experiments to investigate the potential effects of living vegetation and large wood on river morphology, specifically aiming to explore how different wood input and vegetation scenarios impact channel patterns and dynamics. We used a mobile bed laboratory flume, divided into three parallel channels (1.7m wide, 10m long) and filled with uniform sand to reproduce braided networks subject to a series of cycles of flooding, wood input, and vegetation growth. Temporal evolution of river configuration (in terms of the braiding index), vegetation establishment and erosion, and wood deposition amount and pattern was recorded in a series of vertical images. The experiments reproduced many forms and processes that have been observed in the field, from scattered logs in unvegetated, dynamic braided channels to large wood jams associated with river bars and bends in vegetated, stable, single-thread rivers. Results showed that the inclusion of vegetation in the experiments changes wood dynamics, in terms of the quantity that is stored and the depositional patterns that develop. Vegetated banks increased channel stability, reducing lateral erosion and the number of active channels. This promoted the formation of stable wood jams, where logs accumulated continuously at the same locations during subsequent floods, reinforcing their effect on river morphology. The feasibility of studying these processes in a controlled environment opens new possibilities for disentangling the complex linkages in the biogeomorphological evolution of the fluvial system and thus for promoting improved scientific understanding.